3D Graphene Decorated NaTi2(PO4)3 Microspheres as a Superior High‐Rate and Ultracycle‐Stable Anode Material for Sodium Ion Batteries. Issue 19 (15th June 2016) - Fang, Yongjin; Xiao, Lifen; Qian, Jiangfeng; Cao, Yuliang; Ai, Xinping; Huang, Yunhui; Yang, Hanxi
Abstract : 3D graphene decorated NaTi2 (PO4 )3 (NTP@rGO) is successfully synthesized through a facile spray‐drying method. This NTP@rGO material can deliver high reversible capacity (130 mAh g −1 at 0.1 C), superior high‐rate rate capability (38 mAh g −1 at 200 C) and long cycling stability (77% capacity retention after 1000 cycles), suggesting its applicability as a high rate and cycle‐stable anode for the development of high‐power and long cycle life sodium ion batteries for energy storage applications.